Fecal MicroRNAs Show Promise as Noninvasive Crohn's Disease Biomarkers. Issue 1 (14th February 2020) - Wohnhaas, Christian T; Schmid, Ramona; Rolser, Marcel; Kaaru, Eric; Langgartner, Dominik; Rieber, Kathrin; Strobel, Benjamin; Eisele, Claudia; Wiech, Franziska; Jakob, Ines; Gantner, Florian; Herichova, Ivona; et al.
Abstract: Background: Short non-coding microRNAs (miRNAs) are involved in various cellular processes during disease progression of Crohn's disease (CD) and remarkably stable in feces, which make them attractive biomarker candidates for reflecting intestinal inflammatory processes. Here we investigated the potential of fecal miRNAs as noninvasive and translational CD biomarkers. Methods: MiRNAs were screened in feces of 52 patients with CD and 15 healthy controls using RNA sequencing and the results were confirmed by PCR. The relationship between fecal miRNA levels and the clinical CD activity index (CDAI) or CD endoscopic index of severity (CDEIS) was explored, respectively. Additionally, fecal miRNAs were investigated in dextran sodium sulfate, adoptive T-cell transfer, and Helicobacter typhlonius /stress-induced murine colitis models using the NanoString platform. Results: Nine miRNAs (miR-15a-5p, miR-16-5p, miR-128-3p, miR-142-5p, miR-24-3p, miR-27a-3p, miR-223-3p, miR-223-5p, and miR-3074-5p) were significantly (adj. P < 0.05, >3-fold) increased whereas 8 miRNAs (miR-10a-5p, miR-10b-5p, miR-141-3p, miR-192-5p, miR-200a-3p, miR-375, miR-378a-3p, and let-7g-5p) were significantly decreased in CD. MiR-192-5p, miR-375, and miR-141-3p correlated ( P < 0.05) with both CDAI and CDEIS whereas miR-15a-5p correlated only with CDEIS. Deregulated expression of miR-223-3p, miR-16-5p, miR-15a-5p, miR-24-3p, and miR-200a-3p was also observed in murine models. The identified altered fecal miRNA levels reflect pathophysiological mechanisms in CD, such as Th1 and Th17 inflammation, autophagy, and fibrotic processes. Conclusions: Our translational study assessed global fecal miRNA changes of patients with CD and relevant preclinical models. These fecal miRNAs show promise as translational and clinically useful noninvasive biomarkers for mechanistic investigation of intestinal pathophysiology, including monitoring of disease progression. Lay Summary: MicroRNAs are involved in disease progression of Crohn's disease (CD). This study identified significantly altered fecal levels of 17 microRNAs in CD compared to healthy subjects. These microRNAs reflect pathophysiological mechanisms and show promise as clinically useful, noninvasive CD biomarkers.